Epitope mapping of pathogenic leptospira LipL32 - Lottersberger, Javier (2009)
Aims: To identify LipL32 epitopes and to evaluate their capability to recognizespecific antibodies using ELISA.Methods and Results: Epitope mapping by means of a library of overlappingpeptide fragments prepared by simultaneous and parallel solid phase peptidesynthesis on derivatized cellulose membranes (SPOT synthesis) was carried out.Eighty-seven overlapping decapentapeptides corresponding to the completesequence of LipL32 were synthesized. According to spot-image intensities, themost reactive sequences were localized in regions 151?177 (sequenceAAKAKPVQKLDDDDDGDDTYKEERHNK) and 181?204 (sequence LTRIKIPNPPKSFDDLKNIDTKKL).Two peptides (P1 and P2) corresponding tothese sequences were synthesized, and their reactivity evaluated using ELISAtest.Conclusions: Epitope identification and analysis suggested the existence of twoantigenic regions within LipL32. These LipL32 reactive regions were highlyconserved among antigenically variants of Leptospira spp. isolates. Peptidescontaining these regions (P1 and P2) showed a good capability for anti-leptospiralantibody recognition.Significance and Impact of the Study: This finding could have potential relevancenot only for serodiagnosis but also as a starting point for the characterizationof targets for vaccine design.